Real-time control of pig growth through an Integrated management system - Parsons, David J.; Green, D. M.; Schofield, C. P.; Whittemore, C. T. (Elsevier, 2007)
This paper describes the development and testing of the first prototype closed-loop, model-based, real-time system for the integrated control of pig growth and pollutant emissions. In each of two trials, growing pigs were reared from 30–50 to 65–125 kg in groups of 12 in 12 separate pens under controlled environment conditions at ADAS Terrington (Norfolk, England). They were fed ad libitum diets in which the protein content was controlled for each pen. Weight, estimated by visual image analysis, and feed intake were recorded daily for each pig. The control system was based on a mechanistic growth model. Each week, two model parameters were optimised using the data to improve the prediction, then the diet for each pen was optimised by adjusting the crude protein content between 140 and 190 g/kg [dry matter] to minimise the model error from a target for weight or fat depth. Part of the trial set weight gain targets of 50 and 60 kg over 70 days using two pens for each target. In three of the four pens the final mean weight of the pigs was within 2 kg of the target; in the fourth, growth was on target until it was interrupted close to the end of the trial. This trial has demonstrated the potential of the system to control the growth rate of pigs and has given encouraging but not conclusive results for the control of back fat depth.